TINGKAT KEMATANGAN E-GOVERNMENT RSUD WANGAYA MENGGUNAKAN SPBE 2018 - I Gede Indra Suwardika; Gede Rasben Dantes; Gede Indrawan (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTE-government is one of the government's efforts to manage information in the bureaucracy using information technology. Information technology has been implemented in almost all government agencies aimed at reducing costs and time, minimizing corruption in providing services, work effectiveness, transparency, and accountability. E-Gov implementation must be evaluated periodically to find out the level of success and development of e-gov that has been implemented whether it has been running optimally. This research aims to determine the level of e-gov maturity that has been carried out in Wangaya District Hospital. This study uses a mix method that combines qualitative and quantitative methods with 5 respondents selected based on their capabilities. Data collection is done by Participant Observation, interviews, documentation, and questionnaires. Data collection by questionnaire addressed to the management in the general directorate in charge of information technology issues in RSUD Wangaya. Management maturity level analysis uses the 2018 SPBE standard seen in terms of indicators, aspects, and domains. Based on the analysis of the process capability maturity level and the analysis of the capability capability maturity level, a gap level value will be obtained which will be analyzed using Importance Performance Analysis (IPA). The results of the IPA will be a reference for making recommendations that will be proposed to management to make improvements on implementation of e-government in RSUD Wangaya.Keywords: Maturity, E-government, SPBE 2018ABSTRAKE-government merupakan salah satu upaya pemerintah untuk mengelola informasi dalam birokrasi dengan menggunakan teknologi informasi. Teknologi informasi telah dilaksanakn hampir diseluruh in- stansi pemerintah bertujuan untuk mengurangi biaya dan waktu, meminimalkan korupsi dalam mem- berikan pelayanan, efektivitas kerja, transparansi, dan akuntabilitas. Implementasi e-gov harus dieval- uasi secara berkala agar mengetahui tingkat keberhasilan dan perkembangan e-gov yang telah dil- aksanakan apakah sudah berjalan maksimal. Penelitan ini bertujuan untuk mengetahui tingkat kematan- gan e-gov yang telah dilakukan di RSUD Wangaya. Penelitian ini menggunakan mix method yang meng- gabungkan metode kualitatif dan kuantitatif dengan 5 responden yang dipilih berdasarkan kapabilitas yang dimiliki. Pengumpulan data dilakukan dengan cara Participant Observation, wawancara, doku- mentasi, dan kuisioner. Pengumpulan data dengan kuisioner ditujukan kepada pihak manajemen di direktorat umum yang mengurusi masalah teknologi informasi di RSUD Wangaya. Analisis tingkat ke- matangan manajemen menggunakan standarisasi SPBE 2018 yang dilihat dari segi indicator, aspek, dan domain. Berdasarkan analisis tingkat kematangan kapabilitas proses dan analisis tingkat kematangan kapabilitas fungsi akan didapatkan nilai tingkat kesenjangan yang akan dianalisis menggunakan Im- portance Performance Analysis (IPA). Hasil IPA akan menjadi acuan dibuatnya rekomendasi yang akan diusulkan kepada pihak manajemen untuk melakukan perbaikan terhadap implementasi e-government di RSUD Wangaya.Kata Kunci : Tingkat kematangan, E-government, SPBE 2018